FTY720 Exerts Anti-Glioma Effects by Regulating the Glioma Microenvironment Through Increased CXCR4 Internalization by Glioma-Associated Microglia - Guo, Xu-Dong; Ji, Juan; Xue, Teng-Fei; Sun, Yu-Qin; Guo, Ruo-Bing; Cheng, Hong; Sun, Xiu-Lan (Frontiers in Immunology, 2020)
Abstract Background Glioblastoma (GBM) is one of the most malignant and aggressive primary brain tumors. The incurability of glioblastoma is heavily influenced by the glioma microenvironment. FTY720, a potent immunosuppressant, has been reported to exert antitumor effects in glioblastoma. However, the impact of FTY720 on the glioma microenvironment remains unclear. Methods We examined the effects of FTY720 on the distribution and polarization of glioma-associated microglia and macrophages (GAMs) in the glioma-bearing rats using immunofluorescence staining. qRT-PCR and western blotting were used to detect the expressions of CXCR4 and MAPK pathway related signal molecules on microglia in the coculture system. The levels of inflammatory factors were tested via ELISA. Wound healing assay and Matrigel invasion assay were used to determine the migration and invasion of C6 glioma cell. Results We discovered that FTY720 could inhibit the growth, migration, and invasion of glioma by targeting GAMs to impede their effect on glioma cells. Simultaneously, FTY720 could block the chemoattraction of GAMs by inhibiting MAPK-mediated secretion of IL-6 through increased internalization of CXCR4. Moreover, microglia and macrophages are polarized from pro-glioma to an anti-tumor phenotype. Conclusion These results provide novel insights into the inhibitory effects of FTY720 on glioma by targeting GAMs-glioma interaction in the tumor microenvironment.